The role of complement in the immunopathogenesis of acetylcholine receptor antibody-positive generalized myasthenia gravis: bystander or key player? - Michailidou, Iliana; Patsiarika, Anastasia; Kesidou, Evangelia; Boziki, Marina Kleopatra; Parisis, Dimitrios; Bakirtzis, Christos; Chroni, Elisabeth; Grigoriadis, Nikolaos (Frontiers in Immunology, 2025)
The complement system is a key component of the innate immune system. In antiacetylcholine receptor (AChR) antibody-positive (Ab+) generalized myasthenia gravis (MG), complement activation has long been considered a principal driver of pathology. Understanding the role of complement in AChR-Ab+ generalized MG has gained increasing importance in recent years, as anticomplement drugs have been approved for clinical use or are undergoing phase II/III clinical trials. This review aims to discuss recent and previous findings on the role of complement in AChR-Ab+ MG pathology, including its interaction with pathogenic antibodies and mechanisms beyond the classical pathway activation.